2017
DOI: 10.1111/aos.13565
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related macular degeneration: using morphological predictors to modify current treatment protocols

Abstract: To assess predictors of treatment response in neovascular age-related macular degeneration (AMD) in an attempt to develop a patient-centric treatment algorithm. We conducted a systematic search using PubMed, EMBASE and Web of Science for prognostic indicators/predictive factors with the key words: 'age related macular degeneration', 'neovascular AMD', 'choroidal neovascular membrane (CNV)', 'anti-vascular endothelial growth factor (anti-VEGF)', 'aflibercept', 'ranibizumab', 'bevacizumab', 'randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 70 publications
5
60
2
3
Order By: Relevance
“…This study showed CMT improvement after treatment with intravitreal AFL in patients that were poor or non responders to RBZ, as found in other studies [19,20]. However, the group of non responder patients was proven to have a better response to AFL than the group of poor responder patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study showed CMT improvement after treatment with intravitreal AFL in patients that were poor or non responders to RBZ, as found in other studies [19,20]. However, the group of non responder patients was proven to have a better response to AFL than the group of poor responder patients.…”
Section: Discussionsupporting
confidence: 88%
“…The membrane characteristics play a role on treatment outcome. Type 1 [19] and large [20,21] choroidal neovascular membranes were defined as bad predictors for treatment outcome [19] as well as for poor response at 12 weeks [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] A recent meta-analysis covering 2212 subjects found better visual and anatomical outcomes, as well as fewer PRN injections required, in patients without VMT/VMA compared to those with VMT/VMA. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…YBMD insan ömrünün uzamasıyla birlikte çağımızın görme kaybı sebepleri arasında önemli bir yer tutmaktadır. Altmış beş yaş üzerindeki hastaların yaklaşık %10'nu ve 75 yaş üzerindeki hastaların yaklaşık %25'ini etkilemektedir (7)(8)(9). YBMD temelde kuru ve yaş tip olarak ikiye ayrılmaktadır.…”
Section: Introductionunclassified